Obesity and Bone Health: A Complex Link - Hou, Jing; He, Chen; He, Wenzhen; Yang, Mi; Luo, Xianghang; Li, Changjun (Frontiers in Cell and Developmental Biology, 2020)
So far, the connections between obesity and skeleton have been extensively explored, but the results are inconsistent. Obesity is thought to affect bone health through a variety of mechanisms, including body weight, fat volume, bone formation / resorption, proinflammatory cytokines together with bone marrow microenvironment. In this review, we will mainly describe the effects of adipokines secreted by white adipose tissue on bone cells, as well as the interaction between brown adipose tissue, bone marrow adipose tissue and bone metabolism. Meanwhile, this review also reviews the evidence for the effects of adipose tissue and its distribution on bone mass and bone-related diseases, along with the correlation between different populations with obesity and bone health. And we describe changes in bone metabolism in patients with anorexia nervosa or type 2 diabetes. In summary, all of these findings show that the response of skeleton to obesity is complex and depends on diversified factors, such as mechanical loading, obesity type, the location of adipose tissue, gender, age, bone sites, and secreted cytokines, and that these factors may exert a primary function in bone health.